Effect of Different Coconut Water Concentrations on the Growth of Dendrobium spectabile (Blume) Miq. Planlet on MS Media - Santosa, Faradita Azzahra; Setiari, Nintya; Nurchayati, Yulita (Jurnal Ilmu Pertanian Indonesia, 2025)
Dendrobium spectabile is an orchid with unique flowers that are vulnerable to exploitation. Tissue culture is employed to conserve this orchid, where the type of medium and organic supplements significantly affect plantlet growth. Murashige and Skoog (MS) media was added with coconut water as an exogenous hormone source. This study aimed to determine the effect of adding coconut water and determine the optimal concentration to increase the growth of D. spectabile at the subculture stage. The method involved subculturing D. spectabile plantlets in vitro in MS media supplemented with coconut water at concentrations of 0%, 5%, 10%, 15%, and 20%. The research design used a completely randomized design (CRD), with coconut water concentration and ten replicates. Data were analyzed using ANOVA and Duncan’s Multiple Range Test at a 5% significance level. Plantlet growth was observed for two months, and the parameters observed were the emergence of new shoots, leaves, and roots; the number of new shoots, leaves, and roots; and the length of new leaves. The results showed that the addition of coconut water to the subculture medium can increase the leaf growth of D. spectabile orchid plantlets but does not increase shoot and root growth. Coconut water 10% was the most optimal concentration for the number of new leaves and new leaf length. The addition of 15% coconut water was the most optimal concentration for plantlet new leaf emergence. Coconut water plays a vital role in in vitro culture, supporting the various growth processes of D. spectabile plantlets. Keywords: Dendrobium spectabile, ex situ conservation, organic supplement, subculture